The Electrochemical Dissolution of Noble Metals in Alkaline Media - Schalenbach, Maximilian; Kasian, Olga; Ledendecker, Marc; Speck, Florian D.; Mingers, Andrea M.; Mayrhofer, Karl; Cherevko, Serhiy (Electrocatalysis, 2018)
In this study, the electrochemical transient dissolution of polycrystalline silver, gold, iridium, palladium, platinum, rhodium, and ruthenium is examined in 0.05 M NaOH alkaline electrolyte as a function of electrode potential. An inductively coupled plasma mass spectrometer connected to an electrochemical flow cell is used for online detection of the metals dissolution rates. Broad potential windows starting from the hydrogen and going to the oxygen evolution reaction (OER) potentials are used to study the dissolution. The measured dissolution data, such as onsets of dissolution are analyzed and compared with available thermodynamic data. For most metals, at potentials, at which thermodynamics predict metal/solute or metal/oxide transitions, an initiation of the dissolution process is observed. It is suggested that dissolution during metal/oxide transitions is a purely kinetic effect that reflects the solubility of unstable transient oxides. Such oxides can also be formed during the oxygen evolution reaction. The latter fact is used to explain metals dissolution in the region of OER.
Keywords: Dissolution; Corrosion; Noble metals; Mass spectrometry; Electrocatalyst